2011
DOI: 10.3109/13880209.2010.501083
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between phenolic content and antioxidant properties in twenty-four plant species of traditional ethnoveterinary use in the Mediterranean area

Abstract: These findings suggest that phenolic content could be used as an indicator of antioxidant properties. The results of this study encourage investigations on Mediterranean plant species as sources of antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
146
6
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 265 publications
(183 citation statements)
references
References 26 publications
25
146
6
6
Order By: Relevance
“…Statistical analysis was used to find the correlations between antioxidant activities determined by different assays. Strong positive correlation was found between ABTS and DPPH assays (r=0.999), ABTS Several authors have reported a significant positive relationship between the phenolic compounds with their free radical scavenging activity [28,29]. Therefore, the high content of phenolic compounds in diethyl ether extract explains its high antioxidant potential that is evident from its low IC 50 values when compared to other extracts.…”
Section: Correlations Between Antioxidant Assaysmentioning
confidence: 78%
“…Statistical analysis was used to find the correlations between antioxidant activities determined by different assays. Strong positive correlation was found between ABTS and DPPH assays (r=0.999), ABTS Several authors have reported a significant positive relationship between the phenolic compounds with their free radical scavenging activity [28,29]. Therefore, the high content of phenolic compounds in diethyl ether extract explains its high antioxidant potential that is evident from its low IC 50 values when compared to other extracts.…”
Section: Correlations Between Antioxidant Assaysmentioning
confidence: 78%
“…Catechin was used as a standard and the flavonoid content was expressed as g catechin equivalent kg -1 dry weight of plant material (g CE kg -1 DW). Antioxidant capacity was determined by means of ABTS [(2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt)] and DPPH (1,1-diphenyl-2-picrylhydrazyl) assays (Surveswaran et al, 2007) with some modifications (Piluzza and Bullitta, 2011). Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid), a water-soluble analog of vitamin E, was used as the reference standard.…”
Section: Bioactive Compounds and Antioxidant Capacitymentioning
confidence: 99%
“…14,15,16 It was also found that most polar extracting solvents showed more anti oxidant activity and total phenolic content as compared to less polar solvents. It indicate that the polar solvents are important in extracting phytoconstituents with more antioxidant activity and phenolics content which is in agreement with earlier study.…”
Section: Resultsmentioning
confidence: 93%